If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(2x + 3) = (2x + 5)(x + -1) Reorder the terms: X(3 + 2x) = (2x + 5)(x + -1) (3 * X + 2x * X) = (2x + 5)(x + -1) (3X + 2xX) = (2x + 5)(x + -1) Reorder the terms: 3X + 2xX = (5 + 2x)(x + -1) Reorder the terms: 3X + 2xX = (5 + 2x)(-1 + x) Multiply (5 + 2x) * (-1 + x) 3X + 2xX = (5(-1 + x) + 2x * (-1 + x)) 3X + 2xX = ((-1 * 5 + x * 5) + 2x * (-1 + x)) 3X + 2xX = ((-5 + 5x) + 2x * (-1 + x)) 3X + 2xX = (-5 + 5x + (-1 * 2x + x * 2x)) 3X + 2xX = (-5 + 5x + (-2x + 2x2)) Combine like terms: 5x + -2x = 3x 3X + 2xX = (-5 + 3x + 2x2) Solving 3X + 2xX = -5 + 3x + 2x2 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Reorder the terms: 5 + 3X + -3x + 2xX + -2x2 = -5 + 3x + 2x2 + 5 + -3x + -2x2 Reorder the terms: 5 + 3X + -3x + 2xX + -2x2 = -5 + 5 + 3x + -3x + 2x2 + -2x2 Combine like terms: -5 + 5 = 0 5 + 3X + -3x + 2xX + -2x2 = 0 + 3x + -3x + 2x2 + -2x2 5 + 3X + -3x + 2xX + -2x2 = 3x + -3x + 2x2 + -2x2 Combine like terms: 3x + -3x = 0 5 + 3X + -3x + 2xX + -2x2 = 0 + 2x2 + -2x2 5 + 3X + -3x + 2xX + -2x2 = 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 5 + 3X + -3x + 2xX + -2x2 = 0 The solution to this equation could not be determined.
| (x/50)=-11+25 | | x+12527=215+12527 | | 2+2.99999999999999999+0.1=n | | 6/5x^2+7x-70=0 | | -14+10=m-3 | | x-12527=215-12527 | | 2a+6=5a-30 | | 16(2x-1)=4(8x+9) | | 40-x=72 | | 2.561x=-12.36963 | | 2[7-5(1-n)]+5n=-6+2[6(n+1)-3n] | | 4y+y=6y-4y | | -(5x-3)-(4x-7)+6=-7(x-4)-(9x+5)+8 | | 8b+20=9b-6 | | 2x^3=384 | | (-3/-4) | | 4(x+5)=2(2x+1)+18 | | 1/4*(x+3)=4x-2(x-3) | | 13-(2f+2)=2(f-2)+3f | | 7(-4+6x)= | | 5x+17y=-13 | | -2+7=15 | | 49x^2+36y^2=1 | | 7x-2(x-2)=5(x+1)+4 | | 6x+8/15x+20 | | 6(2x-5)=2(6x+1) | | 3(x+5)=2(x-6)+x | | 3n+4=6n-3n-8 | | 7(1-7a)= | | (x-5)(x+4)=2(x-5) | | (x/-3)=-6 | | P=abc |